On the Coronal Palatalization in Early Modern and Present-Day English - Artur Kijak (Anglica. An International Journal of English Studies)
In this paper we look at the case of coronal palatalization [t d s z] > [ʧ ʤ ʃ ʒ] in both Early Modern English (EModE) and Present-day English (PDE) with the aim to determine its major phonological factors (such as the context, triggers, etc.) and to explain the existence of numerous palatalized/unpalatalized variants found in different accents of contemporary English, e.g. [ʧuːn]/[tuːn]/[tjuːn]. It is argued here that the key to understanding the operation of palatalization in contemporary English is the change in the parameter setting which allows/disallows for the merger of two antagonistic elements within a single melodic expression – the *|U I| constraint. This Middle English (ME) innovation guarantees the coronals, to the exclusion of labials and velars, the right to undergo full palatalization. Moreover, the historical perspective adopted in this paper sheds some light not only on the linguistic micro-variation evident in contemporary accents of English, i.e. the existence of [ʧuːn]/[tuːn]/[tjuːn] variants, but also on the absence of front vowels from the group of potential palatalization triggers. It is pointed out that the evolution of the ME diphthong [iu] > [juː], a process which bears a direct responsibility for the later coronal palatalization and the growth of the heterogeneous forms in PDE, is a natural reaction to the *|U I| constraint.